Taxonomy of the dung beetle genus Ochicanthon Vaz-de-Mello (Coleoptera: Scarabaeidae: Scarabaeinae) of the Indian subcontinent, with notes on distribution patterns and flightlessness - Latha, Mathews; Cuccodoro, Giulio; Sabu, Thomas K.; Vinod, K. V. (Zootaxa, 2011)
The taxonomy of the genus Ochicanthon Vaz-de-Mello of the Indian subcontinent is revised and an identification key to the species is provided. The number of Ochicanthon species from the region is increased to 15, eight of which are new: O. besucheti Cuccodoro sp. nov., O. ceylonicus Cuccodoro sp. nov., O. devagiriensis Sabu & Latha sp. nov., O. ernei Cuccodoro sp. nov., O. gauricola Cuccodoro sp. nov., O. murthyi Vinod & Sabu sp. nov., O. mussardi Cuccodoro sp. nov. and O. vazdemelloi Latha & Sabu sp. nov. Four species from the upper montane cloud forests are wingless, raising the number of wingless species of Ochicanthon to five. At least two groups of Ochicanthon exist in the Indian subcontinent: i) the O. tristis group with dorsum predominantly black-brown, with a distinct pattern of orange-yellow patches on the elytra and ii) the O. laetus group with dorsum entirely brown or black and with or without a faint orange patch. The distributions in the moist forests of the southwestern and northeastern regions of the Indian subcontinent, the possible origin of the genus in the Western Ghats in the southwest of the subcontinent and the flightlessness of montane species are discussed.